Women and Russian culture : projections and self-perceptions - Marsh, Rosalind J. (Studies in Slavic literature, culture, and society, 1998)
"This collection of essays by leading Western and Russian specialists contains new insights into and updates previous research on the role of women in Russian culture in the last two centuries, and contributes to two exciting and growing research areas: the feminist critique of work by Russian male authors and the study of Russian women writers.